2017
DOI: 10.22146/jae.22700
|View full text |Cite
|
Sign up to set email alerts
|

Persepsi Pendamping Terhadap Pelaksanaan Program Upsus Pajale Di Daerah Istimewa Yogyakarta

Abstract: In an effort to realize food security, the Ministry of Agriculture made a policy of agricultural development by preparing food self-sufficiency program embodied with Special Effort of Increasing Productivity of Rice, Corn and Soy (UPSUS PAJALE). This escort and assistance is conducted by Agricultural Extension (PNS and THL), BABINSA (Bintara Pembina Desa) and students. This research aim to know 1) the implementation of UPSUS PAJALE program in Yogyakarta Special

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
4
0
3
Order By: Relevance
“…In addition, a research related to companions' perceptions of the implementation of the UPSUS PAJALE (special effort for increasing production of rice, maize and soybean) Program in the Special Region of Yogyakarta has exemplified that perceptions can be influenced by the knowledge. The higher knowledge has a positive impact on the increase in perceptions (Faridhavin et al, 2016). The research confirms that the higher level of perception shows increasingly positive perception.…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations
“…In addition, a research related to companions' perceptions of the implementation of the UPSUS PAJALE (special effort for increasing production of rice, maize and soybean) Program in the Special Region of Yogyakarta has exemplified that perceptions can be influenced by the knowledge. The higher knowledge has a positive impact on the increase in perceptions (Faridhavin et al, 2016). The research confirms that the higher level of perception shows increasingly positive perception.…”
Section: Introductionsupporting
confidence: 71%
“…A research in the Special Region of Yogyakarta has reported that knowledge has a positive influence on the formation of perception. The higher knowledge will support the formation of positive perceptions (Faridhavin et al, 2016). This discrepancy can be caused by the environmental conditions that do not support agricultural activities in the peri-urban areas of Pekalongan City, so that farmers' knowledge is not in accordance with the farmers' expectations to obtain high production yields.…”
Section: Factors Affecting Farmers' Perceptions Of the Agricultural Lmentioning
confidence: 98%
See 2 more Smart Citations
“…Kondisi di lapangan menunjukkan bahwa sesungguhnya pendamping petani lain seperti mahasiswa dan PPL kurang mengetahui tugas dan fungsi dari Babinsa dalam produksi pangan melalui Upsus Pajale. Komunikasi antara pendamping lain dengan Babinsa hanya terjadi saat pertukaran informasi setelah kegiatan pengawalan dan pengawasan (Faridhavin, Witjaksono, & Harsoyo, 2016). Bagi pendamping lain, Babinsa menjalankan peran yang baik dalam melakukan pengawasan penyaluran benih, pupuk, dan alat mesin pertanian (Alsintan).…”
Section: Dari Masa Tanam Sampai Panen Militer Mengasuh Petani DI Slemanunclassified